Remoción quirúrgica del parásito intestinal Prosthenorchis sp. en un mono tití gris (Saguinus leucopus) en cautiverio - Pérez, Janeth; Ramírez, Marcela; Hernández, Carlos (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary This report describes a case report in an adult female white-footed tamarin (Saguinus leucopus), which was confiscated and was moved to Centro de Atención y Valoración de Fauna Silvestre del Área Metropolitana del Valle de Aburrá (CAV) for reeducation purposes. During the clinical and laboratory evaluation the presence of the acanthocephalan Prosthenorchis sp. adult parasites causing intestinal nodules was detected. The presence of this parasite is widely recognized in captive new world monkeys and it is a source of intestinal disease that can be severe and cause animal death. Because of the lack of response to pharmacological treatments over the parasite adult form, a laparotomy and enterotomy procedure was performed for parasites extraction. We describe the preoperative evaluation and management, anesthetic protocol, surgical procedure and post surgical treatment, finishing with complete resolution of clinical signs.